Obesity is not a contraindication to veno-arterial extracorporeal life support. (9th May 2021) - Salna, Michael; Fried, Justin; Kaku, Yuji; Brodie, Daniel; Sayer, Gabriel; Uriel, Nir; Naka, Yoshifumi; Takeda, Koji
Abstract: : OBJECTIVES: Obesity may complicate the peripheral cannulation and delivery of veno-arterial extracorporeal life support (ECLS). With rising global body mass indices (BMI), obesity is becoming increasingly prevalent in severe cardiogenic shock yet its impact on outcomes is not well described. This study sought to examine the relationship between BMI and veno-arterial ECLS outcomes to better inform clinical decision-making. METHODS: All cardiogenic shock patients undergoing peripheral veno-arterial ECLS at our institution from March 2008 to January 2019 were retrospectively analysed ( n = 431). Patients were divided into 4 groups, BMI 17.5–24.9, 25–29.9, 30–34.9 and ≥35 kg/m 2, and compared on clinical outcomes. Multivariable logistic regression was performed to identify variables associated with survival to discharge, the primary outcome of interest. RESULTS: The median BMI was 28.3 kg/m 2 (interquartile range 24.8–32.6) with a range of 17.0–69.1 kg/m 2 . Obese patients achieved significantly lower percentages of predicted flow rates compared with BMI < 25 kg/m 2 patients though did not differ in their lactate clearances. Patients with BMI ≥35 kg/m 2 had similar complication rates to the other cohorts but were more likely to require continuous veno-venous haemodialysis (51% vs 25–40% in other cohorts, P = 0.002). Overall survival to discharge was 48% ( n = 207/431) with no differences between the cohorts ( P = 0.92). Patients with BMI ≥35 kg/m 2 had considerably lower survival (10%) in extracorporeal membrane oxygenation cardiopulmonary resuscitation compared with the other groups ( P = 0.17). On multivariable logistic regression, BMI was not significantly associated with failure to survive to discharge. CONCLUSIONS: In conclusion, with the rising global prevalence of obesity, the results of our study suggest that clinicians need not treat obesity as a negative prognostic factor in cardiogenic shock requiring ECLS.